Family interaction patterns as correlates of bullying behaviour among in-school adolescents in Kwara State - Mustapha, Mulikat Ladi Abdulqadir (2024)
The involvement of parents in different roles in life sometimes affects their communication with their children, which can affect the bullying behaviour of adolescents in school. Therefore, this study examined the patterns of family interaction experienced by respondents and whether such experiences correlate with adolescent bullying in schools in Kwara State, Nigeria. The objectives of this study were to investigate: (i) the perceived family interaction pattern adopted by parents of in-school adolescents; (ii) the prevalence of bullying perpetration and victimisation among in-school adolescents; (iii) the bullying roles of in-school adolescents and (iv) correlation between family interaction patterns, bullying behaviour and bullying roles. The study was a descriptive correlational type study. The sample was 410 adolescent students from 16 proportionally selected secondary schools in Kwara State. An adapted instrument “Family Interaction Patterns and Bullying Behaviour Questionnaire (FIPBBQ)” was used to collect the research data, which has a reliability index of 0.71. The collected data were analysed by frequency, mean rank and PPMC. The study found that school teenagers in Kwara State experienced a positive pattern of family interaction where parents were responsive to their needs and encouraged good behaviour. However, more teenagers in school reported being bullied in the past six weeks. Most of the respondents (50.1%) are bully-victims, 24.0% are abusers and 18.5% are pure victims. Family communication was not significantly related to bullying behaviour. However, there was a significant relationship between family communication patterns and bullying-victimisation role, most especially for females. Based on these findings, recommendations were provided.